ChemInform Abstract: In(OTf)3‐Catalyzed Synthesis of 2‐Styryl Quinolines: Scope and Limitations of Metal Lewis Acids for Tandem Friedlaender Annulation—Knoevenagel Condensation. Issue 23 (June 2015) - Kumar, Dinesh; Kumar, Asim; Qadri, Mohammad Mohsin; Ansari, Md. Imam; Gautam, Abhishek; Chakraborti, Asit K.
Abstract Among a variety of metal Lewis acids evaluated, In/OTf/3 is found to be sole catalyst allowing for the synthesis of 2‐styrylguinones (IV)/(17 examples) by a tandem Friedlaender annulation/Knoevenagel condensation sequence.